The Effect of Guided Inquiry Model Assisted by PhET Simulation on Students' Conceptual Understanding - Wulan Qirani Donita qiran; Skunda Diliarosta; Azza Nuzullah Putri; Ade Sazaliana (Journal of Progressive Science Education, 2026)
Conceptual understanding is an essential competency in science learning because it enables students to interpret scientific phenomena and apply scientific knowledge in everyday life. However, students’ conceptual understanding of vibration and wave concepts at SMP Negeri 24 Padang remained below the expected learning achievement criteria. This study aimed to investigate the effect of the Guided Inquiry learning model assisted by PhET Simulation on students’ conceptual understanding of vibration and wave topics. The study employed a quasi-experimental method using a non-equivalent control group design involving two eighth-grade classes selected through purposive sampling. Data were collected through a conceptual understanding test, classroom observation sheets, and student response questionnaires. The findings revealed that students who learned through Guided Inquiry assisted by PhET Simulation demonstrated better conceptual understanding than those who experienced conventional instruction. The integration of inquiry activities and interactive simulations facilitated students    in exploring scientific phenomena, constructing concepts, and applying their understanding more effectively. These findings suggest that Guided Inquiry assisted by PhET Simulation can be used as an alternative approach to support meaningful and technology-integrated science learning, particularly for abstract science concepts such as vibrations and waves.